The Principal’s Role in Developing Teachers of the Digital Teaching Journal by Using Appsheet at Junior High School - Novianto, Heru; Rasiman, Rasiman; Violinda, Qristin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to describe the principal’s role in developing of teacher’s digital teaching journal by using the AppSheet platform at SMP Negeri 8 Batang, in response to the demands of educational digital transformation. The focus of the study covers four managerial functions of the principal: planning, organizing, actuating, and evaluating. A qualitative approach with a case study design was employed to explore data in depth through interviews, observations, and document analysis involving the principal, the curriculum coordinator, and teachers selected to use purposive and snowball sampling. Data were analyzed by using the Miles and Huberman model through the processes of data reduction, display, and conclusion drawing. The results indicate that the principal plays a strategic role in formulating digitalization policies, forming a development team, allocating tasks based on the competencies, motivating teachers, providing facilities, facilitating training, and innovation. In addition, the principal actively monitors, evaluates, and provides data-driven feedback to enhance system effectiveness. The implementation of AppSheet has proven to accelerate lesson documentation, improve data accuracy, and facilitate real-time supervision, although challenges remain in teachers’ digital literacy and infrastructure limitations. The study concludes that the success of developing a digital teaching journal is determined not only by technology but also by visionary and adaptive school leadership. These findings contribute to strengthening the theory of digital leadership in education and serve as a practical reference for other schools adopting similar innovations.